The Migrant Spirit: Journeys of Faith Beyond the Catholic Church - Genie U. Pedrosa; Dennis V. Madrigal (Philippine Social Science Journal, 2025)
Addressing the increasing trend of young adults leaving the Catholic Church, this qualitative study investigates the motivations and transition experiences of former Catholics in the Philippines who joined other Christian denominations. Through semi-structured interviews and recursive textual analysis, findings reveal that departures were primarily driven by persistent invitations from other groups, limited engagement in Catholic practices, a search for belonging, and dissatisfaction with homilies. While participants faced challenges such as doctrinal confusion and the loss of Catholic friendships, they reported finding spiritual fulfillment and a renewed passion for Scripture in their new communities. These insights highlight critical areas for pastoral reform—specifically regarding youth formation, liturgical quality, and community fellowship—and suggest that future research employ mixed-methods approaches to further understand the dynamics of religious migration.